2003
DOI: 10.1099/vir.0.19263-0
|View full text |Cite
|
Sign up to set email alerts
|

Suppressor activity of potyviral and cucumoviral infections in potyvirus-induced transgene silencing

Abstract: The process known as 'recovery' by which virus-infected plants become resistant to the infection is an interesting phenomenon where both RNA silencing and virus resistance fully converge. In a previous study, we showed that transgenic Nicotiana benthamiana NIbV3 plants, transformed with a mutated NIb coding sequence from Plum pox virus (PPV), showed a delayed, very specific, resistance phenotype, which was induced by the initial infection. This recovery was the consequence of the activation of an RNA silencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 43 publications
1
13
1
2
Order By: Relevance
“…5C). These results are in agreement with a previous report showing that both TVMV and CMV infection reverted virus-induced silencing of N. benthamiana plants transformed with a PPV-derived transgene, but susceptibility to PPV was only restored in the CMV-infected transgenic plants, which suggested that TVMV infection could be eliciting an interpotyvirus cross-protection mechanism [31]. A possible contribution of wild type PPV or TVMV infection to the suppression of amplicon silencing in the 10.6 plants could have been masked by this uncharacterized cross-protection mechanism.…”
Section: Discussionsupporting
confidence: 93%
“…5C). These results are in agreement with a previous report showing that both TVMV and CMV infection reverted virus-induced silencing of N. benthamiana plants transformed with a PPV-derived transgene, but susceptibility to PPV was only restored in the CMV-infected transgenic plants, which suggested that TVMV infection could be eliciting an interpotyvirus cross-protection mechanism [31]. A possible contribution of wild type PPV or TVMV infection to the suppression of amplicon silencing in the 10.6 plants could have been masked by this uncharacterized cross-protection mechanism.…”
Section: Discussionsupporting
confidence: 93%
“…This observation differs from the reports on the silencing-mediated resistance of transgenic N. benthamiana to Potato Virus A or Plum Pox Virus, which was overcome by preinfection with Potato virus Y (Savenkov & Valkonen, 2002) and CMV (Simon-Mateo et al, 2003), respectively.…”
Section: Discussioncontrasting
confidence: 84%
“…This suppressor could reduce, but not eliminate, siRNA in the local and systemic RNA silencing suppression assays (Figures 1-3), suggesting that Pns11 functions similarly to CMV 2b [40] and to turnip yellow mosaic virus p69 [23] , but not to PVY HC-Pro [41] , by interfering with initial stages of RNA silencing. Whether Pns11 could suppress dsRNAinduced RNA silencing was still unknown.…”
Section: Discussionmentioning
confidence: 91%